PENINGKATAN KEMAMPUAN MATEMATIKA PERMULAAN MELALUI PERMAINAN MEMANCING ANGKA PADA ANAK USIA 5-6 TAHUN DI TK MASJID JAMI’ BINTARO JAYA - Sadiah Sri Nurlaily Pipit Mulyaningtias (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research was motivated by a lack of understanding of initial mathematics among children at the Jami' Bintaro Jaya Mosque Kindergarten, who in their original condition had difficulties in understanding the concept of numbers such as the concept of addition. The aim of this research is to describe the process of implementing an introduction to early mathematics for children through a number fishing game. This research uses the classroom action method, the data sources in this research are children and teachers at the Jami' Bintaro Jaya Mosque Kindergarten, while the research data is in the form of observations of the increase in initial mathematics skills in children aged 5-6 years at the Jami' Bintaro Mosque Kindergarten. Jaya, the data collection technique used in this research is in the form of practical tests carried out by children at the Jami' Bintaro Jaya Mosque Kindergarten. From this research there were two cycles, the first cycle was carried out with five meetings, and the second cycle was carried out with five meetings. The results of the first cycle of research showed an average of 56% understanding among children regarding beginning mathematics. Then there was an increase of 23.18% in the second cycle, so that the total increase in knowledge among children at the Jami' Bintaro Jaya Mosque Kindergarten from cycle one and cycle two was 79.18%.